Causality of circulating vitamins on infectious diseases: integrating Mendelian randomization and in vivo evidence - Tang, Aling; Gong, Zhimin; Shi, Yi; Zhang, Weizhen; Jin, Mingming; Sun, Lichao; Chen, Wei (Frontiers in Immunology, 2025)
BackgroundClinical studies have established an association between infections and circulating vitamin levels. However, the relationship stratified by specific pathogen types remains underexplored. More importantly, the causal direction of this association is still unclear.MethodsWe utilized summary-level data from genome-wide association studies (GWAS) of European ancestry, sourced from the UK Biobank (UKB) and FinnGen consortium. A two-sample, bidirectional Mendelian randomization (MR) analysis was employed to investigate the genetic causal relationships between infectious diseases (categorized as bacterial or viral) and circulating levels of vitamins A, B6, B12, C, D, 25-hydroxyvitamin D (25(OH)D), and E. The inverse variance weighted (IVW) method served as the primary analytical approach. Sensitivity analyses were conducted to validate the robustness of the findings. Furthermore, we employed the cecal ligation and puncture (CLP) model in mice to assess the impact of sepsis on serum 25(OH)D levels.ResultsGenetically predicted higher circulating vitamin E levels were associated with an increased risk of viral infection (OR = 1.45, 95% CI: 1.10–1.88). Conversely, genetic predisposition to bacterial infection was associated with lower circulating 25(OH)D levels (OR = 0.96, 95% CI: 0.93–0.99). In vivo experiments confirmed a significant decrease in serum 25(OH)D levels in CLP group mice compared to the Sham group (Sham: 90.7 ± 1.7 vs. CLP: 47.9 ± 5.6). No causal relationships were identified between infections and other vitamins.ConclusionThis study provides evidence for a potential causal link between elevated vitamin E levels and increased susceptibility to viral infection, as well as between bacterial infection and reduced 25(OH)D levels. Furthermore, our in vivo data demonstrated that sepsis (induced by intraperitoneal bacterial infection) led to a significant decrease in serum 25(OH)D levels.